Novel MEK inhibitor trametinib and other retinoblastoma gene (RB)‐reactivating agents enhance efficacy of 5‐fluorouracil on human colon cancer cells. Issue 6 (3rd April 2013) - Watanabe, Motoki; Sowa, Yoshihiro; Yogosawa, Mayumi; Sakai, Toshiyuki
<x xml:space="preserve">Abstract</x> Chemotherapy for colorectal cancer has become more complicated and diversified with the appearance of molecular‐targeting agents. 5‐Fluorouracil (5‐FU) has been a mainstay of chemotherapy for colorectal cancer, but it is still unknown whether the combining of 5‐FU with novel molecular‐targeting agents is effective. Thymidylate synthase (TS) is a direct target of 5‐FU, and the low TS level has been generally supposed to sensitize 5‐FU's efficacy. We therefore hypothesized that RB‐reactivating agents could enhance the efficacy of 5‐FU, because the RB‐reactivating agents could suppress the function of transcription factor E2F of TS gene promoter. We used three RB‐reactivating agents, trametinib/GSK1120212 (MEK inhibitor), fenofibrate (PPARα agonist), and LY294002 (PI3K inhibitor), with 5‐FU against human colon cancer HT‐29 and HCT15 cells. Trametinib induced p15 and p27 expression and reduced cyclin D1 levels in HT‐29 cells. Fenofibrate also dephosphorlated ERK1/2 and reduced cyclin D1 levels in HT‐29 cells. LY294002 induced p27 expression in HCT15 cells. All three agents caused dephosphorylation of RB protein and G1‐phase arrest with a reduction of TS expression. As a consequence, the combination of 5‐FU with each of the agents resulted in a significant decrease of colony numbers in HT‐29 or HCT15 cells. These results suggest "RB‐reactivation therapy" using molecular‐targeting agents to be a new strategy for 5‐FU‐based chemotherapy. In particular, we strongly expect trametinib, which was discovered in Japan and was recently submitted to FDA for approval, to be used together with established regimens for colorectal cancer.